2017
DOI: 10.1016/j.jaap.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Analytical pyrolysis of proteins in samples from artistic and archaeological objects

Abstract: The paper presents a study of proteins found in artistic and archaeological objects based on analytical pyrolysis. Proteins (mainly egg yolk and/or egg white, casein, animal glue and collagen) have been extensively used as paint binders, adhesives and varnishes in mural and easel paintings, and they can be found in archaeological findings, such as bones and skin tissues. In order to overcome limitations of wet chemical methods arising from the reduced solubility of aged proteins in samples of cultural heritage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 93 publications
7
85
0
5
Order By: Relevance
“…[6] 80 %ofthe fragments studied from Te lKabri were part of this group. It has been demonstrated that during aging,p roteinaceous materials become highly thermally stable [20,21] and show very little solubility,c hallenging GC-MS and MS proteomics-based approaches that require an extraction of the proteinaceous material from the matrix. It has been demonstrated that during aging,p roteinaceous materials become highly thermally stable [20,21] and show very little solubility,c hallenging GC-MS and MS proteomics-based approaches that require an extraction of the proteinaceous material from the matrix.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[6] 80 %ofthe fragments studied from Te lKabri were part of this group. It has been demonstrated that during aging,p roteinaceous materials become highly thermally stable [20,21] and show very little solubility,c hallenging GC-MS and MS proteomics-based approaches that require an extraction of the proteinaceous material from the matrix. It has been demonstrated that during aging,p roteinaceous materials become highly thermally stable [20,21] and show very little solubility,c hallenging GC-MS and MS proteomics-based approaches that require an extraction of the proteinaceous material from the matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Thestudy of ancient paintings is asignificant challenge for the analytical chemist. [22][23][24] Evolved gas analysis mass spectrometry (EGA-MS) instead is based on analytical pyrolysis and yields temperature-resolved mass spectrometric information on the gaseous products evolved from samples upon progressive heating.T hough highly degraded samples yield pyrolytic profiles of proteinaceous materials without specificity,h indering the identification of the binder, [20] the technique has the advantage of giving rapid indications regarding the presence of organic media without the need for any sample work-up. [22][23][24] Evolved gas analysis mass spectrometry (EGA-MS) instead is based on analytical pyrolysis and yields temperature-resolved mass spectrometric information on the gaseous products evolved from samples upon progressive heating.T hough highly degraded samples yield pyrolytic profiles of proteinaceous materials without specificity,h indering the identification of the binder, [20] the technique has the advantage of giving rapid indications regarding the presence of organic media without the need for any sample work-up.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few micrograms of the sample mixed with 2 ll of hexamethyl-disilazane (HMDS) was placed in a quartz tube. The detailed working conditions are published elsewhere (Andreotti et al 2009;Lluveras et al 2010;Rampazzi et al 2012;Orsini et al 2017).…”
Section: Chemical Characterization By Py/gc-ms and Ft-irmentioning
confidence: 99%